IT-Helpdesk System Design With Waterfall Model (Case Study : Agung Podomoro Group): IT-Helpdesk System Design With Waterfall Model (Case Study : Agung Podomoro Group) - Siti Nur Khasanah; Sandra Jamu Kuryanti; Hermanto Hermanto; Cep Adiwihardja (Institute of Computer Science (IOCS), 2020)
Agung Security Podomoro Group is a company that uses a lot of electronic inventory, so there are quite a lot of inventory problems that must be dealt with, as long as there is an inventory problem the user or admin of the location submits to Asset Management, by telephone, or other communication tools, then Asset management does and submit to Technical support. Due to the large number of inventory reports that are damaged often the handling of technical support is not handled properly. Therefore it is necessary to have a system that becomes a working benchmark that records damage reports accompanied by a history record so that if there is a similar damage it is easier to handle. In this study a Web-based Help Desk System was designed to deal with existing problems. The website is made based on PHP and uses a MySQL database. The development method that the author uses in designing the web-based Helpdesk System at Agung Podomoro use the Waterfall model.